Clinical and radiological outcomes in 153 patients undergoing oblique corpectomy for cervical spondylotic myelopathy. (January 2014) - Chacko, Ari G.; Turel, Mazda K.; Sarkar, Sauradeep; Prabhu, Krishna; Daniel, Roy T.
Abstract Objective. To document the clinical and radiological outcomes in a large series of patients undergoing the oblique cervical corpectomy (OCC) for spondylotic myelopathy. Materials and methods. We retrospectively analyzed our series of 153 patients undergoing OCC for cervical spondylotic myelopathy (CSM) over the last 10 years. A mean clinical follow-up of 3 years was obtained in 125 patients (81.7%), while 117 patients (76.5%) were followed up radiologically. Neurological function was measured by the Nurick grade and the modified Japanese Orthopedic Association score (JOA). Plain radiographs and magnetic resonance images (MRI) were reviewed. Results. Ninety-two percent were men with a mean age of 51 years and a mean duration of symptoms of 18 months. Sixty-one had a single level corpectomy, 66 had a 2-level, 24 had a 3-level, and two had a 4-level OCC. There was statistically significant improvement (p < 0.05) in both the Nurick grade and the JOA score at mean follow-up of 34.6 ± 25.4 months. Permanent Horner's syndrome was seen in nine patients (5.9%), postoperative C5 radiculopathy in five patients (3.3%), dural tear with CSF leak in one patient (0.7%), and vertebral artery injury in one patient (0.7%). Of the 117 patients who were followed up radiologically, five patients (4.3%) developed an asymptomatic kyphosis of the cervical spine while 22 patients (25.6%) with preoperative lordotic spines had a straightening of the whole spine curvature. Conclusions. The OCC is a safe procedure with good outcomes and a low morbidity for treating cervical cord compression due to CSM. This procedure avoids graft-related complications associated with the central corpectomy, but is technically demanding.